The Pathophysiological Relevance of the iNKT Cell/Mononuclear Phagocyte Crosstalk in Tissues - Cortesi, Filippo; Delfanti, Gloria; Casorati, Giulia; Dellabona, Paolo (Frontiers in Immunology, 2018)
CD1d-restricted Natural Killer T (NKT) cells are regarded as sentinels of tissue integrity by sensing local cell stress and damage. This occurs via recognition of CD1d-restricted lipid antigens, generated by stress-related metabolic changes, and stimulation by inflammatory cytokines, such as IL-12 and IL-18. Increasing evidence suggest that this occurs mainly upon NKT cell interaction with CD1d-expressing cells of the Mononuclear Phagocytic System, i.e., monocytes, macrophages and DCs, which patrol parenchymatous organs and mucosae to maintain tissue homeostasis and immune surveillance. In this review, we discuss critical examples of this crosstalk, presenting the known underlying mechanisms and their effects on both cell types and the environment, and suggest that the interaction with CD1d-expressing mononuclear phagocytes in tissues is the fundamental job of NKT cells.